Safe and Effective Prophylaxis with Bimonthly Intravenous Pentamidine in the Pediatric Hematopoietic Stem Cell Transplant Population. Issue 2 (February 2016) - Levy, Emily R.; Musick, Lisa; Zinter, Matthew S.; Lang, Tess; Cowan, Mort J.; Weintrub, Peggy S.; Dvorak, Christopher C.
Abstract : Background: Without prophylaxis, Pneumocystis jiroveci pneumonia (PCP) develops in 5%–15% of pediatric hematopoietic stem cell transplant (HCT) patients with mortality above 50%. Trimethoprim–sulfamethoxazole is a standard PCP prophylaxis; pentamidine is frequently used as second-line prophylaxis because of trimethoprim–sulfamethoxazole's potential for cytopenias. Monthly intravenous (IV) pentamidine has variable efficacy with PCP infection rates of 0%–10% in pediatric patients, and higher breakthrough rates in those younger than 2 years. We hypothesized that bimonthly (twice monthly) pentamidine might have equivalent safety and improved efficacy; therefore, we conducted a retrospective analysis of bimonthly pentamidine PCP prophylaxis. Methods: We retrospectively reviewed records of all pediatric HCT patients who received bimonthly IV pentamidine between December 2006 and June 2013, and collected data regarding demographics, clinical course, prophylaxis rationale, laboratory values and adverse events. Results: Between December 2006 and June 2013, 111 pediatric HCT patients received bimonthly IV pentamidine (574 doses, 8758 patient-days); 31 patients were younger than 2 years at initiation. In the majority (53% of courses), pentamidine was initiated because of cytopenias. Fourteen patients (12.6% of patients, 2.4% of doses) experienced a side-effect prompting discontinuation, including 3 patients with infusion-related hypotension/anaphylaxis and 3 with acute pancreatic dysfunction. No patients [0% (95% confidence interval: 0–3.2)] developed PCP during or after bimonthly IV pentamidine prophylaxis. Conclusions: Bimonthly IV pentamidine for PCP prophylaxis in the HCT pediatric population has comparable safety to monthly IV pentamidine and was highly effective, including in the very young. Bimonthly IV pentamidine should be considered in pediatric patients as second-line PCP prophylaxis.